Mitigasi Perubahan Iklim dalam Mempertahankan Produktivitas Tanah Padi Sawah (Studi kasus di Kabupaten Indramayu) - Chairul Muslim (Jurnal Penelitian Pertanian Terapan, 2013)
Impact of Climate Change (DPI) in West Java, especially the agricultural sector (food) are strongly influenced by the shift early growing season occurs 2 to 4 weeks since last 5 years. Some areas on the North Coast (North Coast of Java) early season retreat 1 to 2 months. As a result it affects the decline in production and productivity of rice, the price fluctuations of agricultural products and food insecurity disturbing. Purpose of the study looked at the impact of climate change on the productivity of rice paddy fields at the time of drought and floods and how the wisdom of farmers to cope with climate change. The research location Indramayu regency, as it is the central areas of rice-based food production, and the area has the insecurity of the impacts of climate change. The results showed the presence of DPI on the applied local wisdom flooded farmers (a) using the short-lived rice varieties, (b) rice varieties resistant varieties will be flooded and planted in one stretch with monoculture cropping systems. (C) use a pump to remove water . Dry season activities were implemented: (a) promote the planting schedule, (b) create a nursery, (c) use early maturing varieties, (d) cross dams, (e) motion to eradicate rats, (f) spray white butterfly pests (borers rods), (g) irrigation cultivation rationed sleigh, (h) conduct ceremonies (salvation alms earth), (i) and down motion field simultaneously. Productivity of rice under normal conditions GKP 5 tons gkp / ha (R / C 2.21). While the impact of flooded rice productivity on average only up to 3.5 tonnes gkp/ ha (R / C 1.01). Impact of drought rice productivity was only 4 quintals / ha (R / C 0:24). To overcome this required specific technologies and institutional development, and agricultural infrastructure, to support sustainable food self-sufficiency. Keywords: Mitigation. Climate Change, Productivity. wetland